71.2k views
16 votes
If using the method of completing the square to solve the quadratic equation

x2 -9x + 2 = 0, which number would have to be added to "complete the square"?

User Phil Peace
by
5.5k points

1 Answer

4 votes

Answer:

Add the square of half of the coefficient of
x to both sides


\left(-\frac92\right)^2=(81)/(4)

Completing the square:

Rewrite
x^2-9x+2=0 in the form
y=(x-b)^2 +c

Add the square of half of the coefficient of
x to both sides:


\implies x^2-9x+2+\left(-\frac92\right)^2=\left(-\frac92\right)^2


\implies x^2-9x+2+(81)/(4)=(81)/(4)


\implies\left(x-\frac92\right)^2 +2=(81)/(4)


\implies\left(x-\frac92\right)^2 +2-(81)/(4)=0


\implies\left(x-\frac92\right)^2 -(73)/(4)=0


\implies\left(x-\frac92\right)^2 -(73)/(4)=0

User Bobharley
by
5.9k points